Compliance of Prolanis Gymnastics Participants Against Hypertension Prevention at Johan Pahlawan Health Center, West Aceh District - Lusi Aprilia Sunarma; Zakiyuddin (Sean Institute, 2023)
Hypertension is a circulatory system disorder that causes an increase in blood pressure above the normal value, which exceeds 140/90 mmHg. This hypertension can also cause damage to the body's organs, either directly or indirectly. This study uses a quantitative method with a cross-sectional approach and is analyzed analytically. The population in this study were all prolanis gymnastics participants at the Johan Pahlawan Health Center club, totaling 33 people, namely 27 women and 6 men. The sampling technique is to use total sampling technique. This research was conducted at the Johan Pahlawan Health Center which is located at Jalan Rundeng Village, Johan Pahlawan District, West Aceh Regency. Which was done on January 18, 2023. The results of the study using the chi-square test found that there was a relationship between distance (0.044<0.05) time (0.001<0.05) motivation (0.008<0.05) with the adherence of prolanis gymnastics participants to the prevention of hypertension at the Johan Pahlawan Health Center, West Aceh District. The conclusion in this study is that there is a relationship between distance, time, motivation with the adherence of prolanis exercise participants to the prevention of hypertension at the Johan Pahlawan Health Center, West Aceh District. Suggestions are expected for health workers, especially the Johan Pahlawan Health Center to be able to provide counseling or information related to the importance of participating in prolanis gymnastics as a form of prevention against hypertension. 05) with the adherence of prolanis gymnastics participants to the prevention of hypertension at the Johan Pahlawan Health Center, West Aceh District. The conclusion in this study is that there is a relationship between distance, time, motivation with the adherence of prolanis exercise participants to the prevention of hypertension at the Johan Pahlawan Health Center, West Aceh District. Suggestions are expected for health workers, especially the Johan Pahlawan Health Center to be able to provide counseling or information related to the importance of participating in prolanis gymnastics as a form of prevention against hypertension. 05) with the adherence of prolanis gymnastics participants to the prevention of hypertension at the Johan Pahlawan Health Center. Suggestions are expected for health workers, especially the Johan Pahlawan Health Center to be able to provide counseling or information related to the importance of participating in prolanis gymnastics as a form of prevention against hypertension.